Five weeks of dynamic finger flexor strength training on bouldering performance and climbing-specific strength tests. A randomized controlled trial - Saeterbakken, Atle Hole; Bratland, Erik; Andersen, Vidar; Stien, Nicolay (Frontiers in Physiology, 2024)
The aim of the study was to examine the effects of a 5-week dynamic finger flexor strength training program on bouldering performance and climbing-specific strength tests. Advanced to elite level boulderers (n=31) were randomized to a dynamic finger strength training group (DFS) or a control group (CON). The DFS training program consisted of 3 weekly sessions (3-5 sets, 4-10 repetitions per session). Both groups continued bouldering training as usual throughout the intervention period. Pre-and post-intervention measures included bouldering performance, maximal dynamic finger strength, isometric finger strength (peak and average force), and rate of force development (RFD). The DFS demonstrated greater improvement in dynamic finger strength (11.5%, 3.9kg) than the CON (5.3%, 1.7kg; p = 0.075, ES = 0.90), but there were no differences between the groups in 1RM (p = 0.075, ES = 0.67), bouldering performance (p = 0.39, ES = 0.35), isometric finger strength (p = 0.42 -0.56, ES = 0.20 -0.22) or RFD (p = 0.30, ES = 0.46). The DFS improved dynamic (p < 0.01, ES = 1.83) and isometric peak and average (p < 0.01, ES = 0.98, and p < 0.01, ES = 0.75, respectively) finger strength, while the CON only increased dynamic finger strength (p < 0.05, ES = 0.58). None of groups improved bouldering performance or RFD (p = 0.07 -0.58). In conclusion, 5 weeks of DFS training improving dynamic strength to a greater extent than bouldering alone in addition to improving isometric finger strength among advanced boulderers. Isolated bouldering improved dynamic finger flexor strength, but importantly, increased finger strength (dynamic or isometric) did not improve bouldering performance.